Information security handbook develop a threat model and incident response strategy to build a strong information security framework - Death, Darren (Packt Publishing, 2017)
This book is for security analysts and professionals who deal with security mechanisms in an organization. If you are looking for an end to end guide on information security and risk analysis with no prior knowledge of this domain, then this book is for you.